2021
DOI: 10.1038/s41598-021-88429-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the dopaminergic system in the reward-related behavior of pregabalin

Abstract: There has been an increase in cases of drug addiction and prescription drug abuse worldwide. Recently, pregabalin abuse has been a focus for many healthcare agencies, as highlighted by epidemiological studies. We previously evaluated the possibility of pregabalin abuse using the conditioned place preference (CPP) paradigm. We observed that a 60 mg/kg dose could induce CPP in mice and that pregabalin-rewarding properties were mediated through glutamate neurotransmission. Notably, the dopaminergic reward circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 108 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…This neuronal population is important for behavior, cognition, and motor activity. Our previous study suggested that the dopaminergic system could be affected by pregabalin administration [ 10 ]. In the present study, we identified that pregabalin at therapeutic doses (10 μM) had no impact on the survivability of neurons [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neuronal population is important for behavior, cognition, and motor activity. Our previous study suggested that the dopaminergic system could be affected by pregabalin administration [ 10 ]. In the present study, we identified that pregabalin at therapeutic doses (10 μM) had no impact on the survivability of neurons [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear whether pregabalin at therapeutic doses causes abnormalities in the fetus and hampers its development [ 9 ]. Previously, we showed that pregabalin induces behavioral sensitization through the dopamine reward system, which suggests that pregabalin could have an effect on dopaminergic neurons [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These drugs not only block the development of hyperalgesia and central sensitization, but also inhibit the release of excitatory neurotransmitter, including glutamate, norepinephrine (noradrenaline), serotonin, and dopamine ( Hendrich et al, 2008 ; Eroglu et al, 2009 ). The dopamine reward system may play a role in gabapentinoid abuse and addiction ( Althobaiti et al, 2021 ). The hippocampus, with abundant alpha - 2 / delta-1 subunit of voltage-gated calcium channels, plays an essential role in processing declarative memories and working memory ( Yonelinas, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the other neural populations, VM neurons are known to have early and late developmental stages. Our recent investigation hypothesized that gabapentinoids could affect the dopaminergic neuronal system ( Althobaiti et al, 2020 , 2021 ). In the current study, we observed that gabapentin at therapeutic doses has no impact on the survivability of VM neurons.…”
Section: Discussionmentioning
confidence: 99%